A comprehensive review of coconut shell powder composites: Preparation, processing, and characterization. (December 2022) - Nadzri, Seri Nur Iman Hidayah Ahmad; Sultan, Mohamed Thariq Hameed; Shah, Ain Umaira Md; Safri, Syafiqah Nur Azrie; Talib, Abdul Rahim Abu; Jawaid, Mohammad; Basri, Adi Azriff
Coconut shell is an agricultural residue, usually disposed of through open burning. Toxic gases have been emitted from the open burning phase and can therefore be detrimental to human health and the environment. Thus, to reduce the risk of pollution, researchers have developed a new technology by using agro-wastes to produce biocomposites. Coconut shell powder (CSP) is a solid nonfood waste, which can be potentially exploited to reduce the usage of synthetic fiber. Coconut shell is also low-cost and low weight material that can be used to reduce the production cost of and fuel consumption for transportation. This review has focused on the research carried out on the CSP loaded into different types of matrices, highlighting the fundamental, mechanical, physical, and thermal properties of CSP composites. This article also provides critical review of the development for CSP composite and the summary of the results presented in the literature, focusing in the properties of CSP with polymeric matrices and the application design for economical products.